Pengembangan Aplikasi Go Social Berbasis Android sebagai Media Pembelajaran IPS pada Materi Kedatangan Bangsa-Bangsa Barat ke Indonesia Kelas VIII di SMP Negeri 11 Semarang - Trihartini, Dian; Ginanjar, Asep (Universitas Negeri Semarang, 2021)
Learning media is a tool that can be used by students to understand the material presented by the teacher. Innovation in the use of learning media that uses many visual aspects will help students understand the material more than just text narratives. This android-based go social application learning media contains material for the history of SMP class VIII, namely material for the arrival of western nations to Indonesia. The type of research used is development research, using the ADDIE model. The results showed that the android-based go social application as a social study learning media was included in the very feasible and very practical criteria to be used as a learning medium with an assessment obtained of 89.41% from material experts, 86.66% from media experts, and 97.32% of the student response questionnaire. It is hoped that the results of this study can be further developed and can meet the needs of class VIII SMP students in the future.